2022
DOI: 10.3390/healthcare10071289
|View full text |Cite
|
Sign up to set email alerts
|

Gold Medals, Silver Medals, Bronze Medals, and Total Medals: An Analysis of Summer Paralympic Games from 1992 to 2016

Abstract: The Paralympic Games (PG) are considered one of the biggest events in the world, with increasing coverage by media and participation. The present study aimed to investigate the variation in the number of gold, silver, bronze, and totals medals in the Summer PG from 1992 to 2016. Data related to the results were extracted from the International Paralympic Committee to an SPSS database. Descriptive statistics and Friedman’s two-way analysis of variance by ranks were used to check the differences across medals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
0
0
1
Order By: Relevance
“…Ludwig Guttmann. En el año 1944, se incluyó la práctica deportiva en los procesos de rehabilitación, como un medio para rehabilitar el cuerpo y la mente, además de contribuir a la reinserción en la sociedad (Jacinto et al, 2022;Mauerberg-de Castro et al, 2016;Santos et al, 2022;Webborn & Van de Vliet, 2012). La participación de las PeSD en actividades deportivas se reconoce como un protocolo vital en su rehabilitación, es así como los profesionales de la salud han utilizado el deporte como una herramienta terapéutica (Blauwet & Willick, 2012;24(2), julio-diciembre, 1-15. https://doi.org/10.29035/rcaf.24.2.11 CAF 24(2) | 3 Mauerberg-de Castro et al, 2016;Santos et al, 2023;Tweedy et al, 2018;Wilson & Ramchandani, 2017).…”
Section: Introductionunclassified
“…Ludwig Guttmann. En el año 1944, se incluyó la práctica deportiva en los procesos de rehabilitación, como un medio para rehabilitar el cuerpo y la mente, además de contribuir a la reinserción en la sociedad (Jacinto et al, 2022;Mauerberg-de Castro et al, 2016;Santos et al, 2022;Webborn & Van de Vliet, 2012). La participación de las PeSD en actividades deportivas se reconoce como un protocolo vital en su rehabilitación, es así como los profesionales de la salud han utilizado el deporte como una herramienta terapéutica (Blauwet & Willick, 2012;24(2), julio-diciembre, 1-15. https://doi.org/10.29035/rcaf.24.2.11 CAF 24(2) | 3 Mauerberg-de Castro et al, 2016;Santos et al, 2023;Tweedy et al, 2018;Wilson & Ramchandani, 2017).…”
Section: Introductionunclassified
“…It was observed that several external factors could influence performance indicators, including an increase in the number of participants and greater and better government investment. Additionally, it was noted that preparation should be based on a multidisciplinary team, meaning that improvement in performance relies on knowledge and investment from governments [21].…”
mentioning
confidence: 99%